Comparative effect of PNF VS early Dynamic stretching in pain, range of motion and functional status in shoulder joint - Fatima Khalid, Umar Abdul Rehman Khalid, Laila Niaz Khan, Sumbal Salik, Arslan Saeed, Zainab Abdullah, Sania Maqbool, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Burn of shoulder and axillary region are common affecting patient’s range of motion and his/her performance in his daily life. Because post burn if treatment is not given, contracture will ultimately form. Aim: To determine the comparative effectiveness of PNF (hold relax) VS early Dynamic stretching exercises for improving pain, range of motion and functional status in the shoulder joint and quality of functional recovery in burn patients. Methodology: A single blinded Randomized clinical trial was conducted at Mayo Hospital, Burn ward. Total 74 patients (Male and Female) were included in the study on the basis of inclusion and exclusion criteria. Participants were randomly allocated in two groups, 32 in each group by odd even method. Group 1 received PNF (hold-relax) protocol while group 2 received Dynamic stretching protocol, both the groups received the treatment along with conventional therapy on alternate days for 4 weeks. Pre and post treatment assessment VAS, Q-DASH score and ranges of motion were done. Data was analyzed using SPSS 23 version. Paired sample T-test and independent sample T test was used to assess within and between group analysis with having confidence interval CI 95% and p value 0.05. The purpose of paired T-test and independent t-test was to determine the difference within and between the groups in all clinical parameters (Q-DASH score, VAS score and ROM) during both pre and post treatment. Results: According to the findings, VAS, Q-DASH scoring and ranges of affected burn shoulder joint were significantly improved in both groups i.e., treated with PNF and Dynamic stretching protocol. However, on group comparison; statistically significant improvement in VAS, Q-DASH scoring and ranges of shoulder were observed in patients treated with PNF as compared to Dynamic stretching with p-value <0.05. Practical implication: The study provides the opportunity to physiotherapist to get aware of the role of PNF and dynamic stretching in preventing and treating post burn patients. It provides the statistical effectiveness of techniques in increasing the recovery rate of patients by using defined treatment protocol. Conclusion: This study proved that PNF and Early Dynamic Stretching both are effective in improving pain, range of motions and functional status among burn patients. However; PNF (hold relax) was more beneficial for improving functional status and treating pain and range of motion in shoulder joint of burn patients with p-value <0.05. Keywords: Axillary burns, Contractures, Early Dynamic Stretching exercises, Functional recovery, Range of motion(ROM).